Assessment of language policy of the people of Kazakhstan: results of a sociological study - А. Сатыбаева; А. Шабденова; В. Кузьменков (Хабаршы. Психология және социология сериясы)
This article presents the results of sociological analysis of the population's assessment of the language policy in the Republic of Kazakhstan. The main purpose of the research is to study the opinions of different social categories of Kazakhstani people on the issues of language policy conducted in the country. The results of the sociological survey conducted by the Language Policy Committee of the Ministry of Science and Higher Education of the Republic of Kazakhstan (for 2021-2023) were the theoretical basis for this study.